Frailty Combined with Loneliness or Social Isolation: An Elevated Risk for Mortality in Later Life. Issue 11 (23rd July 2020) - Hoogendijk, Emiel O.; Smit, Annelot P.; van Dam, Carmen; Schuster, Noah A.; de Breij, Sascha; Holwerda, Tjalling J.; Huisman, Martijn; Dent, Elsa; Andrew, Melissa K.
Abstract : BACKGROUND/OBJECTIVES: Frailty, loneliness, and social isolation are all associated with adverse outcomes in older adults, but little is known about their combined impact on mortality. DESIGN: Prospective cohort study. SETTING: The Longitudinal Aging Study Amsterdam. PARTICIPANTS: Community‐dwelling older adults aged 65 and older (n = 1, 427). MEASUREMENTS: Frailty was measured with the frailty phenotype (Fried criteria). Loneliness was assessed with the De Jong Gierveld Loneliness Scale. Social isolation was operationalized using information on partner status, social support, and network size. Two categorical variables were created, for each possible combination regarding frailty and loneliness (FL) and frailty and social isolation (FS), respectively. Mortality was monitored over a period of 22 years (1995–2017). Survival curves and Cox proportional hazard models were used to study the effects of the FL and FS combinations on mortality. Analyses were adjusted for sociodemographic factors, depression, chronic diseases, and smoking. RESULTS: Frailty prevalence was 13%, and 5.9% of the sample were frail and lonely, and 6.2% frail and socially isolated. In fully adjusted models, older adults who were only frail had a higher risk of mortality compared with people without any of the conditions (hazard ratio [HR] range = 1.40–1.48; P  < .01). However, the highest risk of mortality was observed in people with a combined presence of frailty and loneliness or social isolation (HRFL = 1.83; 95% confidence interval [CI] = 1.42–2.37; HRFS = 1.77; 95% CI = 1.36–2.30). Sensitivity analyses using a frailty index based on the deficit accumulation approach instead of the frailty phenotype showed similar results, confirming the robustness of our findings. CONCLUSION: Frail older adults are at increased risk of mortality, but this risk is even higher for those who are also lonely or socially isolated. To optimize well‐being and health outcomes in physically frail older adults, targeted interventions focusing on both subjective and objective social vulnerability are needed.